Mikroplavalci na osnovi Marangonijevega pojava - Kovač, Klemen (Matrika, 2019)
Article consists of two parts. In first part of the article surface phenomena in liquids are presented, which results in Marangoni effect. First of all surface tension, which is the engine of this phenomenon, and stress tensor in liquids are introduced, introduction of which enables derivation of boudary conditions on liquid surface. Conditions for static equilibrium on surface are analyzed and when dynamics comes into play. In second part of the article self-propelling emulsion droplet is analyzed. Movement is consequence of induced Marangoni flow on border between droplet and outside fluid, which is the result of nonhomogenious surface tension of droplet. Velocity field is calculated, inside, outside and on surface of droplet, also velocity of our droplet is determined. In the end two possible ways to establish nonhomogenious profile of surface tension are presented and mechanism behind it is analyzed.
Keywords: eng; hidrodinamika; hydrodynamics; Marangoni effect; Marangonijev pojav; microswimmers; mikroplavalci; površinska napetost; surface tension